SPEAKING SKILL IS THE FOCUS OF ENGLISH LANGUAGE TEACING AT ALL LEVELS - Sutiyono, Akhmad (LPPM STKIP PGRI Bandar Lampung, 2012)
The main objective of teaching English as a Foreign Language is enables students to use English for communication in real-life situations. However, it is a fact that many students find difficulties in mastering English. They cannot speak English well although they have learned English for years. It is the teachers’ responsibility to encourage students to practice their English at least in the classroom hours. The English teachers should apply various teaching techniques and teaching media that over higher and wider opportunities to use English in real-life situations.All kinds of instructional activities and exercises provided by the English teachers should offer and challenge students to use English orally so that they will not be afraid of making mistakes in their speaking.